Measurement of damage in systemic vasculitis: a comparison of the Vasculitis Damage Index with the Combined Damage Assessment Index. Issue 1 (24th August 2010) - Suppiah, Ravi; Flossman, Oliver; Mukhtyar, Chetan; Alberici, Federico; Baslund, Bo; Brown, Denise; Hasan, Nadeem; Holle, Julia; Hruskova, Zdenka; Jayne, David; Judge, Andrew; Little, Mark A; et al.
Abstract : Objectives: To compare the Vasculitis Damage Index (VDI) with the Combined Damage Assessment Index (CDA) as measures of damage from vasculitis. Methods: A total of 283 patients with vasculitis from 11 European centres were evaluated in a cross-sectional study using the VDI and CDA. Results: Wegener's granulomatosis (58.4%) and microscopic polyangiitis (11.0%) were the most common diagnoses. Agreement between VDI and CDA scores (Spearman's correlation) was 0.90 (95% CI 0.87 to 0.92). There was good correlation between individual comparably evaluated organ systems (Spearman's correlation 0.70–0.94). Interobserver reliability (assessed by intraclass correlation coefficient (ICC)) was 0.94 (95% CI 0.89 to 0.98) for VDI and 0.78 (95% CI 0.63 to 0.93) for CDA. Intraobserver reliability was 0.92 (95% CI 0.83 to 1.00) for VDI and 0.87 (95% CI 0.75 to 1.00) for CDA. A total of 13 items were not used in the VDI compared to 23 in the CDA. Observers agreed that the CDA covered the full spectrum of damage attributable to vasculitis but was more time consuming and thus possibly less feasible for clinical and research purposes. Conclusions: The VDI and CDA capture reliable data on damage among patients with vasculitis. The CDA captures more detail but is more complex and less practical than the VDI. Further evolution of damage assessment in vasculitis is likely to include key elements from both instruments.